2002
DOI: 10.1016/s0735-1097(01)01736-3
|View full text |Cite
|
Sign up to set email alerts
|

Isolated neonatal ductus arteriosus aneurysm

Abstract: There is a higher incidence of DAA with a good outcome in our series compared with previous reports. We speculate that the presence of DAA may be a normal variant of the ductal bump and part of a normal process of spontaneous ductal closure in full-term neonates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(27 citation statements)
references
References 19 publications
0
27
0
Order By: Relevance
“…[47] It is rare for symptomatic DAA to manifest within 24 hours of birth,[23] and the symptoms are commonly due to complications like spontaneous rupture, thromboembolism, infection, erosion into airways, or compression of adjacent thoracic structures. [2357] But in our series, all the four neonates had presented a few hours after birth with stridor and feeble cry on account of compression of adjacent thoracic structures by a large DAA; their giant size (maximum internal mean diameter of 15.9 ± 3.5 mm) probably is the reason for the early presentation. Although all four neonates presented with symptoms within 24 hours after birth, only one required surgery.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…[47] It is rare for symptomatic DAA to manifest within 24 hours of birth,[23] and the symptoms are commonly due to complications like spontaneous rupture, thromboembolism, infection, erosion into airways, or compression of adjacent thoracic structures. [2357] But in our series, all the four neonates had presented a few hours after birth with stridor and feeble cry on account of compression of adjacent thoracic structures by a large DAA; their giant size (maximum internal mean diameter of 15.9 ± 3.5 mm) probably is the reason for the early presentation. Although all four neonates presented with symptoms within 24 hours after birth, only one required surgery.…”
Section: Discussionmentioning
confidence: 61%
“…Thrombus formation was noted in 30% of cases in the series of Jan et al . [5] CT scan and magnetic resonance imaging (MRI) are useful tools to delineate the extent of DAA and degree of compression of the surrounding structures. [5] Two of the cases in our study group underwent CT scan of the thorax which demonstrated compression of left main bronchus in one and thrombus formation in the other.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A ductus arteriosus aneurysm is a congenital cardiac abnormality with an 8.8% reported incidence among full-term neonates. 1 ) Ductus arteriosus aneurysms diagnosed in the neonatal period are often asymptomatic and have a benign natural course, resulting in spontaneous regression and disappearance in most cases. 1 , 2 ) Rarely, a ductus arteriosus aneurysm may present with symptoms requiring medical attention.…”
Section: Introductionmentioning
confidence: 99%
“… 1 ) Ductus arteriosus aneurysms diagnosed in the neonatal period are often asymptomatic and have a benign natural course, resulting in spontaneous regression and disappearance in most cases. 1 , 2 ) Rarely, a ductus arteriosus aneurysm may present with symptoms requiring medical attention. Reported symptoms include thromboembolism, infection, compression of an adjacent structure, and spontaneous rupture.…”
Section: Introductionmentioning
confidence: 99%